2018
DOI: 10.18240/ijo.2018.02.02
|View full text |Cite
|
Sign up to set email alerts
|

Anti-fibrotic effect of rosmarinic acid on inhibition of pterygium epithelial cells

Abstract: This study demonstrate that RA could inhibit fibrosis of PECs by down-regulating type I collagen expression and TGF-β1/Smad signaling. Therefore, RA is a potent therapeutic agent for the treatment of pterygium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Coculture of human amniotic mesenchymal stem cells (hAMSCs) with pterygium fibroblasts also showed the anti-EMT effect by inhibition of α-smooth muscle actin. Also, proximity with hAMSCs led to a diminution in the migratory an antifibrotic effect in pterygium (Chen et al, 2018).…”
Section: Wnt Pathway and Tgfβ Signaling In Pterygiummentioning
confidence: 94%
See 2 more Smart Citations
“…Coculture of human amniotic mesenchymal stem cells (hAMSCs) with pterygium fibroblasts also showed the anti-EMT effect by inhibition of α-smooth muscle actin. Also, proximity with hAMSCs led to a diminution in the migratory an antifibrotic effect in pterygium (Chen et al, 2018).…”
Section: Wnt Pathway and Tgfβ Signaling In Pterygiummentioning
confidence: 94%
“…As a result, these cells acquire a migratory and invasive phenotype (Kalluri & Weinberg, ; Lamouille, Xu, & Derynck, ). EMT transition, which has a role in fibrosis and pterygium is a fibrotic lesion (Chen et al, ). Variety of transcription factors including SNAIL , twist‐related protein ( TWIST ), zinc finger E‐box binding homeobox ( ZEB ), and E47 are key regulators of EMT since they act on downregulation of epithelial‐specific genes and overexpression of genes related to mesenchymal phenotype (Nisticò, Bissell, & Radisky, ; Savagner, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo et al (20) reported that RA had an antiinflammatory effect on acute lung injury by decreasing the levels of pro-inflammatory molecules. Chen et al (21) showed that RA ameliorated the fibrosis of pterygium epithelial cells by decreasing type I collagen production and downregulating TGF-β1/Smad signaling.…”
Section: )mentioning
confidence: 99%
“…Up to now, surgery was the main treatment for pterygium [ 16 ]. Fibrosis causes adherence of the conjunctiva and Tenon's capsule, which may lead to recurrence, and it is dependent on the patient's inflammatory response [ 17 ]. The recurrence rate of simple excision results in high recurrence from 24% to 89%.…”
Section: Discussionmentioning
confidence: 99%